Gut microbiota and irritable bowel syndrome: status and prospect - Cheng, Xinyu; Ren, Cheng; Mei, Xiaofei; Jiang, Yufeng; Zhou, Yafeng (Frontiers in Medicine, 2024)
Irritable bowel syndrome (IBS) is a very common gastrointestinal disease that, although not as aggressive as tumors, affects patients' quality of life in different ways.The cause of IBS is still unclear,but more and more studies have shown that the characteristics of the gut microbiota, such as diversity, abundance, and composition, are altered in patients with IBS, compared to the healthy population, which confirms that the gut microbiota plays a crucial role in the development of IBS. This paper aims to identify the commonalities by reviewing a large body of literature. Changes in the characteristics of gut microbiota in patients with different types of IBS are discussed, relevant mechanisms are described, and the treatment modalities of gut microbiota in IBS are summarized. Although there are more clinical trials that have made good progress, more standardized, more generalized, larger-scale, multi-omics clinical studies are what is missing. Overall, gut microbiota plays a crucial role in the development of IBS, and there is even more potential for treating IBS by modulating gut microbiota.